Determination of natural and synthethic estrogenic compounds in coastal lagoon waters by HPLC-Electrospraymass Spectrometry - Pojana, G.; Bonfa, A.; Busetti, Francesco; Collarin, A.; Marcomini, A. (Taylor & Francis, 2004)
A new analytical method was developed for the simultaneous determination of estrogenic compounds of natural (estradiol, estriol, estrone) and synthetic origin, both steroidal (ethinylestradiol, mestranol) and non-steroidal (benzophenone, bisphenol-A, diethylstilbestrol, octylphenol, nonylphenol, nonylphenol monoethoxylate carboxylate), in environmental aqueous samples by high-performance liquid chromatography coupled with ion trap-mass spectrometry via electrospray interface (HPLC-ESI-IT-MS). Quantitative MS detection was performed in the negative mode for all compounds except mestranol and benzophenone, which were detected under positive ion conditions. Very low method detection limits (MDLs), between 0.1 and 2.6 ng/L, were achieved in coastal lagoon water samples, while the developed solid-phase-extraction (SPE) procedure permitted simultaneous recovery of all analytes from spiked water samples with yields >70% (7-11 RSD%), except estriol and benzophenone, which were recovered with 60% (9 RSD%) and 50% (11 RSD%) yields, respectively. The proposed method was applied to the analysis of Venice (Italy) lagoon waters, where average concentrations of selected compounds in the 2.8-33 ng/L concentration range were found.